Pengaruh Model Pembelajaran Listening Team terhadap Keterampilan Berbicara Siswa Kelas V SDN 03 Salimpaung - Della Livia; Wilda Fathia; Ilhamni Desrina (CV Berkah Syahdin Trust, 2026)
This Research is based on the low speaking skills of students.the casual factor of this condition is the learning model used to make students bored so that it makes students not optimal in expressing ideas using the correct sentence sequence, and interrupted speech patterns, making the messeges conveyed difficult to understand. The main contributing factor to this condition is the learning model that tends to be monotonous, resulting in students not being optimal in expressing ideas using correct sentence structure, appropriate vocabulary selection, and supporting facial expressions when speaking. The purpose of this study is to find out the influence of the application of the Listening Team learning model on the speaking skills of students in grade V to 03 Salimpaung. This research method is quantitative with an experimental approach, using pre-experimental design with one group Pretest-Posttest design type. The reseach subject include all V grade students totaling 17 people as both population and sample. Sample selection was conducted through total sampling technique. The data collection instrumens used include performance tests to measure students speaking skills applied at the beginning and end of the learning process. Data analysis was conducted through prerequisite tests and hypothesis testing using paired sample t-test. The research findings show that the average Pretest score obtained was 63.75, while the average Posttest score reached 87.94. These result are strengthened by the t-test which shows a significance value < α (0.000 < 0.005). This means there is a positive impact from the implementation of the Listening Team. This the Listening Team model can be used as one of the learning models in learning to speak in Indonesian language subjects.